Pengaruh E-WOM, Keamanan dan Desain Situs Web terhadap Kepercayaan Serta Implikasinya terhadap Keputusan Membeli pada E-Commerce di Indonesia - K. Dima Surya; Ketut Arnaya (Jurnal Manajemen dan Bisnis, 2017)
ABSTRACTThe purpose of this study is to determine the influence of trust, e-wom, security, and web site design on purchase decisions on tokopedia.com. The data analysis is use Structure Equation Modeling technique with the AMOS 24 program. The conclusion of the analysis shows that the trust and website design variables have positive and significant effect on the purchase decision, while e-wom and security do not affect the purchase decision. Thus, tokopedia.com can pay attention to the security features and design of its website to increase the confidence and decision to buy its customers.